2013
DOI: 10.2337/db13-1150
|View full text |Cite
|
Sign up to set email alerts
|

SLC30A8 Nonsynonymous Variant Is Associated With Recovery Following Exercise and Skeletal Muscle Size and Strength

Abstract: Genome-wide association studies have identified thousands of variants that are associated with numerous phenotypes. One such variant, rs13266634, a nonsynonymous single nucleotide polymorphism in the solute carrier family 30 (zinc transporter) member eight gene, is associated with a 53% increase in the risk of developing type 2 diabetes (T2D). We hypothesized that individuals with the protective allele against T2D would show a positive response to short-term and long-term resistance exercise. Two cohorts of yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Thus, even though SLC30A8 is not expressed in liver or muscle, Tamaki and colleagues have shown that the SNP is associated with altered insulin clearance, as assessed by C-peptide/insulin ratios, consistent with their KO mouse data [82]. Similarly, Sprouse et al [99] reported that the SNP is associated with altered muscle function, perhaps suggesting that ZnT8 influences communication between β cells and other tissues. The fact that these fundamental questions remain to be addressed indicates that much still remains to be learned about ZnT8.…”
Section: Concluding Remarks and Future Perspectivessupporting
confidence: 53%
“…Thus, even though SLC30A8 is not expressed in liver or muscle, Tamaki and colleagues have shown that the SNP is associated with altered insulin clearance, as assessed by C-peptide/insulin ratios, consistent with their KO mouse data [82]. Similarly, Sprouse et al [99] reported that the SNP is associated with altered muscle function, perhaps suggesting that ZnT8 influences communication between β cells and other tissues. The fact that these fundamental questions remain to be addressed indicates that much still remains to be learned about ZnT8.…”
Section: Concluding Remarks and Future Perspectivessupporting
confidence: 53%
“…Variants of single nucleotide polymorphism in ZnT8 gene have been associated with differences in muscle phenotype and function in men (Sprouse et al 2014). The positive relationship between ZIP7 gene expression and total physical activity level found in the current study may be reflective of the function of this particular zinc transporter in skeletal muscles.…”
Section: Discussionmentioning
confidence: 65%
“…This discrepancy requires further investigation. The SNP rs13266634 is implicated as a key determinant in humoral autoreactivity to ZnT8 (443) and is also related to a favorable cardiometabolic lipid profile in human immunodeficiency virus (HIV)/ hepatitis C virus-coinfected patients (322) and skeletal muscle strength and size (383).…”
Section: Single Nucleotide Polymorphism and Gene Dosage Effects Ofmentioning
confidence: 99%